2009
DOI: 10.1007/s00296-009-1005-5
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis: scientific development from a critical point of view

Abstract: Rheumatoid arthritis (RA) is classified as a chronic, progressive, systemic autoimmune disorder leading to inflammation, stiffness, defective position and destruction of joints. Finally a complete loss of mobility and functioning can be the result. The fraction of disability varies strongly, for example, a systematic review shows a 50% disability in a period from first occurrence to disability from 4.5 to 22 years. Scientific efforts focused strongly on therapeutic and diagnostic methods during recent years. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
7
14
0
9
Order By: Relevance
“…The increase in the number of landmark publications during this time period likely reflects the emergence of new diagnostic techniques, changes in classification criteria, and the increased availability of highly effective therapies that exploit the perturbed inflammatory pathways thought to be responsible for the disease . These findings are concordant with the other bibliometric analyses published in rheumatology that have shown similar trends . This pattern also aligns with publications from other medical specialties that have demonstrated peak time periods of highly cited papers during the same time interval .…”
Section: Discussionsupporting
confidence: 79%
“…The increase in the number of landmark publications during this time period likely reflects the emergence of new diagnostic techniques, changes in classification criteria, and the increased availability of highly effective therapies that exploit the perturbed inflammatory pathways thought to be responsible for the disease . These findings are concordant with the other bibliometric analyses published in rheumatology that have shown similar trends . This pattern also aligns with publications from other medical specialties that have demonstrated peak time periods of highly cited papers during the same time interval .…”
Section: Discussionsupporting
confidence: 79%
“…The most productive institutions were located in the USA, which had the highest citation rate of all publishing countries. The dominant role of American research found in this study has been described in studies of research output in other scientific areas [6,7]. Interestingly, some countries, such as Brazil, Saudi Arabia and Tunisia, had detectable results in the analysis of international cooperation although they are not as well-established in the field.…”
Section: Resultssupporting
confidence: 54%
“…The number and distribution of publishing countries was comparable to the one found in other medical fields (heart disease, scoliosis, psoriasis, and rheumatoid arthritis),[30323536] with the most prolific countries situated in North America and Europe. All top five countries were from these regions, with the USA being the most prolific.…”
Section: Discussionsupporting
confidence: 56%